Creation of demand through value chain development in millets - Rao, B Dayakar; Reddy, K Nirmal; Rajendraprasad, M P; Hymavathi, T V; Ganapathy, K N (Indian Farming, 2023)
Millets (small-grained cereals including, sorghum, pearl millet, and other small millets) are known for their hardiness and adaptation to low input and harsh environments of Asia and Africa. They are major means of sustainable livelihood of poor in the dryland regions of the country providing both food and fodder requirement. However, their area has declined from 36.34 million ha (1955-56) to 17.0 million ha (2011-12). The major causal factors responsible for such a decline in area of millet crops are; relatively higher demand and profitability of competing crops, lower market prices of millets vs. competing crops many of which are artificially supported, declining role as a food crop at aggregate level, urbanization, and income growth. One of the important determinants of millets economy is the consumption parameter. The consumption of millets in general declined overtime.